High-strength and high-corrosion-resistance magnesium alloy based on corrosion thermodynamics and design method thereof

Through the design method based on corrosion heat-kinetics, alloy elements are screened and magnesium alloy components are optimized, and the problem of difficulty in improving the corrosion resistance and strength of magnesium alloys is solved, and the development of high-strength and high-corrosion magnesium alloys is achieved, reducing development costs and cycles.

CN119811556AActive Publication Date: 2025-04-11NORTHEASTERN UNIV CHINA

Patent Information

Application Number
CN202411861534.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to improve the corrosion resistance and strength of magnesium alloys at the same time, and the corrosion resistance of high-strength magnesium alloys is poor, while the mechanical properties of corrosion-resistant magnesium alloys are insufficient, resulting in huge challenges in the development of high-strength high-corrosion magnesium alloys.

Method used

Using a design method based on corrosion thermal-kinetics, we use the design method to establish a data set, screen alloy elements, determine candidate alloy elements, and optimize the alloy components using the corrosion performance prediction model to form a dense protective film to improve the corrosion resistance of magnesium alloys.

Benefits of technology

It has achieved significant improvement in corrosion resistance of magnesium alloys on the basis of retaining high mechanical strength, reducing development cycles and costs, and simplifying the design process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119811556A_ABST
    Figure CN119811556A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of magnesium alloy materials, and discloses a high-strength and high-corrosion-resistance magnesium alloy based on corrosion thermodynamics and a design method thereof. The design method comprises the following steps: establishing a data set according to the existing high-strength magnesium alloy, and determining a first micro-alloy element and low-alloy element candidate set; based on corrosion thermodynamics and dynamics, screening a first micro-alloy element and low-alloy element candidate set from the angle of asynchronous dissolution and deposition of alloy elements and magnesium elements, and determining a second micro-alloy element and low-alloy element candidate set; according to the two element candidate sets, candidate alloy elements are determined, and candidate alloys are formed according to predefined mass percentage contents of the candidate alloy elements; and the candidate alloy is verified and subjected to component optimization through a corrosion performance prediction model, and the high-strength and high-corrosion-resistance magnesium alloy is obtained. The design method disclosed by the invention is simple, convenient and rapid, low in cost and high in reliability, and can efficiently guide the design of preparing the high-strength and high-corrosion-resistance magnesium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium alloy materials, and in particular to a high-strength and high-corrosion-resistant magnesium alloy based on corrosion thermo-dynamics and a design method thereof. Background Art

[0002] Magnesium alloys have low density, high specific strength, good damping and excellent processing performance, and are widely used in aerospace, transportation, and electronic products. However, the insufficient strength and poor corrosion resistance of traditional magnesium alloys have seriously hindered the further development of magnesium alloys. Severe plastic deformation can significantly improve the strength of magnesium alloys, but the deformation process is relatively complicated.

[0003] Preparation of protective coating and improvement of corrosion resistance of magnesium alloy substrate are commonly used methods to improve the corrosion resistance of magnesium alloy, but once the coating breaks, it will cause severe local corrosion. Alloying is often used to improve the corrosion resistance and mechanical properties of magnesium alloy. However, most studies only focus on corrosion resistance or only on mechanical properties. Moreover, the corrosion resistance of high-strength magnesium alloys is often poor, while the mechanical properties of corrosion-resistant magnesium alloys are usually insufficient. The development of high-strength and high-corrosion-resistant magnesium alloys still faces huge challenges. At present, the design of high-strength and high-corrosion-resistant magnesium alloys mostly adopts trial and error methods, lacks corresponding theoretical guidance, and is difficult to succeed at one time. In addition, the trial and error method is used to find new magnesium alloy materials in a huge material space, facing the problems of long development cycle and high cost, and requires a lot of manpower and material resources. Summary of the invention

[0004] In order to solve the technical problems that the above-mentioned prior art is difficult to improve the corrosion resistance and strength of magnesium alloys at the same time, and there are long experimental cycles and high experimental costs, the present invention provides a simple, fast, low-cost, and labor- and material-saving high-strength and high-corrosion-resistant magnesium alloy based on corrosion thermodynamics and a design method thereof.

[0005] The high-strength and high-corrosion-resistant magnesium alloy based on corrosion thermodynamics and the design method thereof of the present invention are realized by the following technical solutions:

[0006] The first object of the present invention is to provide a design method for a high-strength and high-corrosion-resistant magnesium alloy based on corrosion thermodynamics, comprising the following steps:

[0007] Step 1, obtain the alloying element composition and mechanical properties of the disclosed magnesium alloy, use the corresponding data of the mechanical properties as input, and use the alloying element composition as the corresponding output to establish a data set; wherein the alloying element composition includes the type of alloying element and the content of alloying element.

[0008] Step 2: Using the required mechanical properties as constraints, the data set is screened to obtain a high-strength magnesium alloy system data set.

[0009] Step 3: Based on the constraint condition that the content of the alloying element is ≤ the first threshold, the alloying elements in the high-strength magnesium alloy system data set are evaluated and screened to obtain a candidate set of the first micro-alloying element and the low-alloying element.

[0010] Step 4, based on corrosion thermodynamics and kinetics, from the perspective that asynchronous dissolution and deposition of alloying elements and magnesium elements can promote the formation of a protective film during corrosion, with the constraints that micro-alloying elements satisfy a late dissolution order and an early deposition order, and low-alloying elements satisfy a dissolution order and a deposition order between the micro-alloying elements and magnesium elements, the alloying elements in the high-strength magnesium alloy system data set are screened to obtain a second micro-alloying element and a low-alloying element candidate set.

[0011] Step 5: Determine candidate alloying elements based on the first candidate set of microalloying elements and low alloying elements and the second candidate set of microalloying elements and low alloying elements, and compose candidate magnesium alloys according to the predefined alloying element mass percentages.

[0012] Step 6, using the corrosion performance prediction model, determine the nucleation rate and growth rate of the candidate magnesium alloy corrosion product, as well as the corrosion rate and corrosion depth of the alloy. With the nucleation rate of the corrosion product > the corresponding growth rate, the corrosion rate ≤ the second threshold, and the corrosion depth < the third threshold as constraints, the candidate magnesium alloy is screened to obtain a high-strength and high-corrosion-resistant magnesium alloy.

[0013] It should be noted that in the above step 1, in order to facilitate the screening of the alloying element composition of the magnesium alloy that can meet the required mechanical property requirements based on the mechanical property data of the magnesium alloy, the present invention first establishes a data set based on the disclosed mechanical property data of the magnesium alloy as input and the alloying element composition as the corresponding output.

[0014] It should be noted that, in some preferred embodiments of the present invention, since the present invention mainly focuses on the role of alloying elements in precipitation strengthening and fine grain strengthening, the above-mentioned mechanical property data include data on mechanical strength contribution and plasticity contribution, so that the data on mechanical strength contribution and plasticity contribution can be input to obtain a high-strength magnesium alloy system data set.

[0015] In the above step 2, when obtaining the data of the disclosed magnesium alloys, the present invention mainly focuses on the role of alloying elements in precipitation strengthening and fine grain strengthening, so as to evaluate and screen the commonly used alloying elements in magnesium alloys according to the two constraints of mechanical strength and plasticity, and use the screened alloying elements as the high-strength magnesium alloy system data set.

[0016] In the above step 3, the present invention obtains a first micro-alloying element and a low-alloying element candidate set whose content of the alloying element is ≤ the first threshold value from the high-strength magnesium alloy system data set according to the commonly used content of the alloying element, so as to facilitate further screening and determination of the candidate alloying elements in the subsequent steps. Wherein, in some preferred embodiments of the present invention, the first threshold value is 10.0%, that is, the content of the alloying element is ≤10.0% as a constraint condition to obtain the first micro-alloying element and the low-alloying element candidate set. Wherein, in some more preferred embodiments of the present invention, the alloying element content is ≤1.0% and 10.0%≥the alloying element content>1.0% is used as a constraint condition to screen the alloying elements in the high-strength magnesium alloy system data set, and obtain the first micro-alloying element and the low-alloying element candidate set whose content of the micro-alloying element is ≤1.0% and 10.0%≥the low-alloying element content>1.0%.

[0017] In the above step 4, the present invention is based on corrosion thermodynamics and kinetics, and takes into account the standard electrode potential E corresponding to the metal of the element, from the perspective that the asynchronous dissolution and deposition of alloy elements and magnesium elements can promote the formation of a protective film during the corrosion process. θ The more positive the value, the later the metal will dissolve. Therefore, the standard electrode potential of each alloy element in the high-strength magnesium alloy system data set can be calculated, and then the dissolution order of the alloy elements can be determined according to the size of the standard electrode potential. Therefore, in some preferred embodiments of the present invention, the present invention proposes to obtain the standard electrode potential of the metal corresponding to the alloy element, and sort the standard electrode potential of the metal corresponding to each alloy element in descending order according to its value, so as to obtain the dissolution order of the atoms corresponding to each alloy element.

[0018] In some preferred embodiments of the present invention, the present invention takes into account the solubility product K of the element corresponding to the oxide or hydroxide sp The corresponding critical deposition line is drawn by the value of . The lower the critical deposition line, the more preferential deposition occurs. Therefore, the solubility product K of the corresponding oxide or hydroxide of each alloy element can be queried and calculated. sp , and then the deposition order of the alloy elements can be determined according to the height of the critical deposition line of the oxide or hydroxide corresponding to each alloy element. Therefore, the present invention proposes to examine the solubility product of the oxide and hydroxide corresponding to each alloy element containing magnesium in the high-strength magnesium alloy system data set, and sort them in order according to the height of the critical deposition line of the oxide or hydroxide corresponding to each alloy element, that is, to obtain the deposition order of magnesium alloy corrosion products. Among them, in some preferred embodiments of the present invention, taking the Mg-Gd-Y-Zr-In alloy system as an example, the deposition phase diagram of each alloy element in the Mg-Gd-Y-Zr-In alloy is drawn with pH as the horizontal coordinate and ion concentration as the vertical coordinate, and the deposition order of the alloy elements is determined by the height of the critical deposition line of each substance in the deposition phase diagram.

[0019] The present invention takes into account that the speed of alloy element dissolution can be judged according to the standard electrode potential, and the critical deposition line of the corrosion product can feedback the deposition order of the corrosion product during the corrosion process. Therefore, according to the dissolution order of the corresponding atoms of each alloy element and the deposition order of the corrosion product of the magnesium alloy, the micro-alloy element satisfies the dissolution order at the back and the deposition order at the front, and the low-alloy element satisfies the dissolution order and deposition order between the micro-alloy element and the magnesium element as the constraint condition, to realize the screening of the alloy elements of the magnesium alloy, so that the candidate magnesium alloy system obtained by screening can be passivated and improve its corrosion resistance. For example, in some preferred embodiments of the present invention, In and Zr are selected as micro-alloy elements, and Gd and Y are selected as low-alloy elements, so as to utilize the asynchronous dissolution and deposition of the low-alloy elements Gd and Y, the micro-alloy elements In and Zr, and the Mg element, and utilize the step-by-step amplification nucleation mechanism to densify the protective film generated during the corrosion process, form a multi-layer protective film, realize alloy passivation, and improve the corrosion resistance of the alloy. Among them, low-alloy elements Gd and Y play the role of solid solution strengthening and precipitation strengthening, micro-alloy element Zr plays the role of grain refinement, and In as a micro-alloy element can preferentially deposit to promote the deposition effect of other elements and inhibit the anodic dissolution kinetics of the alloy.

[0020] In step 5 of the present invention, the present invention starts from the alloying element content and corrosion thermodynamics and kinetics, and by removing the intersection of the first microalloying element, low alloying element candidate set and the second microalloying element, low alloying element candidate set, respectively determines the type and content of the final microalloying element and the final low alloying element, and then combines them with the Mg element according to the predefined alloying element mass percentage to form a candidate magnesium alloy. In a preferred embodiment of the present invention, the composition of the determined candidate magnesium alloy is: Gd 1.0% to 10.0%, Y1.0% to 10.0%, Zr 0.01% to 1.0%, In 0.01% to 1.0%, and the rest is Mg, totaling 100%.

[0021] In order to ensure that the candidate magnesium alloy obtained above can retain or improve the mechanical strength of the Mg-Gd-Y-Zr alloy, the present invention obtains the Mg-Gd-Y-Zr-In alloy by adding the trace element In, so as to further utilize the asynchronism of the dissolution and deposition of the low alloy elements Gd and Y, the micro alloy elements In and the Mg element, and utilize the step-by-step amplification nucleation mechanism to densify the protective film generated during the corrosion process, form a multi-layer protective film, realize alloy passivation, and improve the corrosion resistance of the alloy. Therefore, the present invention also determines the nucleation rate and growth rate of the corrosion products of the candidate magnesium alloy, as well as the corrosion rate and corrosion depth of the alloy through the corrosion performance prediction model. In addition, the present invention takes into account that the speed of alloy element dissolution can be judged according to the standard electrode potential, and the deposition order of the corrosion products in the corrosion process can be fed back according to the critical deposition line of the corrosion products, so the screening of alloy elements of the magnesium alloy can be realized according to these two constraints. However, whether a dense passivation film can be formed under these two constraints is related to the alloy composition design, so it is necessary to further examine the two constraints of corrosion rate and corrosion depth of magnesium alloy by establishing a corrosion performance prediction model as the final discriminant factor for determining the alloy design procedure. The corrosion resistance of the magnesium alloy was further verified and optimized through the established corrosion resistance prediction model.

[0022] Therefore, when establishing the corrosion performance prediction model in step 6, the present invention considers the four aspects of dissolution, ionization, diffusion and deposition, and calculates the corrosion performance of the candidate magnesium alloy by calculating the ion concentration, corrosion product supersaturation, corrosion product nucleation rate and growth rate, corrosion depth and corrosion rate in the corrosion dissolution process, which can be used to verify and optimize the composition of the candidate magnesium alloy. Specifically, by establishing a "dissolution-ionization" model and a "diffusion-deposition" model, the current density of the magnesium alloy at the corrosion potential is investigated by the "dissolution-ionization" model, and the corrosion depth of the magnesium alloy at the corrosion potential is investigated by the "diffusion-deposition" model. After calculating the results of Mg-Gd-Y-Zr-In alloys with different preset alloy compositions, the candidate magnesium alloy is screened with the constraint that the nucleation rate of the corrosion product is much greater than its corresponding growth rate, the corrosion rate drops rapidly to ≤ the second threshold value over time, and the corrosion depth <5μm as the constraint conditions, and the suitable high-strength and high-corrosion-resistant magnesium alloy composition is determined. Among them, in some preferred Mg-Gd-Y-Zr-In embodiments of the present invention, the second threshold is 1 mm / a, that is, the corrosion rate drops rapidly to ≤1 mm / a over time as a constraint. In some preferred embodiments of the present invention, the third threshold is 5 μm, that is, the corrosion depth <5 μm is used as a constraint.

[0023] In some preferred embodiments of the present invention, the "dissolution-ionization-diffusion-deposition" model is obtained by the following steps:

[0024] 1) Taking the standard electrode potential of the metal corresponding to each element of the candidate magnesium alloy as input, presetting the composition of the Mg-Gd-Y-Zr-In alloy, and calculating the equilibrium potential of the metal electrode reaction corresponding to each element according to the Nernst equation. Then taking the equilibrium potential of the metal electrode reaction corresponding to each element as input, the corrosion potential of the magnesium alloy is calculated according to the mixed potential theory. Then taking the corrosion potential of the magnesium alloy as input, the corrosion current density of the magnesium alloy under the corrosion potential is calculated according to the Butler-Volmer formula.

[0025] 2) Taking the solubility product of the corresponding oxides and hydroxides of each element as input, according to Faraday's law and Fick's second law, the supersaturation S of each corrosion product is calculated. Taking the supersaturation S of each corrosion product as input, the nucleation rate and growth rate of the corresponding corrosion product are calculated. Taking the nucleation rate and growth rate of the corrosion product as input, the coverage of the corrosion product and the overall corrosion rate of the magnesium alloy are calculated.

[0026] The corrosion current density of the magnesium alloy under the corrosion potential is obtained by the following steps:

[0027] The present invention takes into account that the corrosion of magnesium alloys involves metal oxidation and hydrogen reduction. The corrosion potential of magnesium alloys is jointly affected by the type of alloying elements and the equilibrium potential. First, the equilibrium potential of the metal electrode reaction corresponding to each element is calculated according to the Nernst equation, and then the corrosion potential of the magnesium alloy is calculated according to the mixed potential theory. The calculation formulas involved are shown in Formulas 1 to 8:

[0028] R→O+ne Formula 1.

[0029]

[0030]

[0031]

[0032] E a =E c =E corr Formula 5.

[0033] In formula 1, R is a reduced substance; O is an oxidized substance; e is an electron transferred by the electrode reaction; and n is the number of electrons transferred by the electrode reaction.

[0034] In formula 2, E e is the equilibrium potential of the metal electrode reaction corresponding to each element; E θis the standard potential of the metal electrode reaction corresponding to each element; R is the gas constant; T is the temperature, the unit is K; [O] is the concentration of the oxidized substance; F is the Faraday constant, 96485C / mol; [R] is the concentration of the reduced substance.

[0035] In formula 3, i a (E a ) indicates i a Equivalent to E a , is the total anode potential; f Mk is the atomic percentage of the kth alloying element in the magnesium alloy; i a,Mk (E a ) is the anodic potential of the kth alloying element in the magnesium alloy; k is the number of total alloying elements in the magnesium alloy.

[0036] In formula 4, i c (E c ) indicates i c Equivalent to E c , is the total cathode potential; f Mk is the atomic percentage of the kth alloying element in the magnesium alloy; i c,Mk (E c ) is the cathode potential of the kth alloying element in the magnesium alloy; k is the number of total alloying elements in the magnesium alloy.

[0037] In formula 5, E a is the total anode potential; E c is the total cathode potential; E corr is the corrosion potential.

[0038] The current density under the corrosion potential is calculated by the Butler-Volmer formula, and the speed of alloy element dissolution is determined by the current density. The number of dissolved layers is then calculated based on the dissolution model, and the number of dissolved layers is converted into dissolution current density. The calculation formulas are shown in Equations 6 to 8. When the slowest dissolving element accumulates a layer on the surface, the corrosion potential needs to be corrected and the dissolution current density needs to be recalculated.

[0039] η=E corr -E formula 6.

[0040]

[0041]

[0042] In formula 6, η is the overpotential, E corr is the corrosion potential, and E is the actual tested potential.

[0043] In formula 7, i M is the current density under corrosion potential; i M,0is the exchange current density; α is the symmetry coefficient; n is the number of electrons transferred by the electrode reaction; F is the Faraday constant, 96485C / mol; η is the overpotential; R is the gas constant; T is the temperature, in K.

[0044] In formula 8, J i is the dissolution current density, L i is the number of dissolved equivalent layers.

[0045] In some preferred embodiments of the present invention, the coverage of corrosion products and the overall corrosion rate of the magnesium alloy are specifically obtained by the following steps:

[0046] First, according to Faraday's law and Fick's Second Law The relationship between the ion concentration and pH value at the metal / solution interface and time is calculated together, and then the supersaturation S of each corrosion product is calculated. When the supersaturation > 1, the corrosion product will nucleate and grow on the metal surface. Supersaturation S and nucleation rate V N The calculation formula is as follows:

[0047]

[0048]

[0049]

[0050] In formula 9, S is the supersaturation of corrosion products; [M n+ ] is the concentration of metal ions; [OH - ] is OH - The concentration of; n is the number of electrons transferred by the electrode reaction; K sp is the solubility product of corrosion products.

[0051] In equations 10 and 11, V N is the homogeneous nucleation rate; V N ' is the heterogeneous nucleation rate; A is the composite constant that varies with temperature; γ is the surface energy corresponding to the critical nucleation size, 0.1 J / m 2 ; v is the molecular volume; S is the supersaturation of corrosion products; k is the reaction constant, 0.1 mol / Ls; T is the temperature, the unit is K.

[0052] The growth of the crystal follows a two-dimensional step growth mode, and the corresponding crystal growth rate calculation formula is as follows:

[0053]

[0054] In formula 12, V R is the crystal growth rate; A is a composite constant that varies with temperature and is set to 10 24; B is the composite constant that varies with temperature and is set to 10 3 ; S is the supersaturation of corrosion products.

[0055] Due to the continuous deposition of corrosion products, the alloy surface will be gradually covered, thereby preventing further corrosion of the magnesium matrix. The current density of the film area and the non-film area is different, so the overall corrosion rate of the alloy can be expressed by the coverage of the corrosion product film, and the coverage of the corrosion product film is calculated by the following formula:

[0056] i corr =i alloy (1-θ)+i CS θ Formula 13.

[0057] In formula 13, i corr is the corrosion current density of magnesium alloy; the current density of the area with corrosion products and the area without corrosion products are represented by i cs and i alloy ; θ is the coverage of the corrosion product film.

[0058] The corrosion depth mentioned in the present invention refers to the dissolution depth of the alloy when the corrosion product film completely covers (coverage>0.99) the metal surface. The corrosion depth can be obtained by integrating the curve of the corrosion rate changing with time, and the calculation formula is as follows:

[0059]

[0060] Where CD is the corrosion depth; i corr is the corrosion current density of the alloy; t is the time, unit is s.

[0061] In some preferred embodiments of the present invention, the chemical composition of the high-strength and high-corrosion-resistant magnesium alloy obtained by the above-mentioned design method of the present invention consists of the following components in percentage by mass: Gd 6%, Y 3%, Zr 0.5%, In 0.5%, and the rest is Mg, totaling 100%.

[0062] In the Mg-Gd-Y-Zr-In alloy system designed by the present invention, during the corrosion process of the Mg-Gd-Y-Zr-In alloy, Mg and low alloy elements Gd and Y are preferentially dissolved, and In is dissolved last, and then the corrosion products containing In are preferentially deposited, so that the corrosion products of Gd and Y are transformed from homogeneous nucleation to heterogeneous nucleation, reducing their nucleation surface energy by 2 / 3 and promoting their deposition effect, and then the deposition effect of Mg(OH)2 is further amplified by the corrosion products of Gd and Y, and finally a dense protective film with a multi-layer structure is formed on the surface of the alloy, thereby improving the corrosion resistance of the alloy.

[0063] The present invention also provides a method for preparing a high-strength and high-corrosion-resistant Mg-Gd-Y-Zr-In alloy with multi-objective design from the perspective of corrosion thermodynamics, comprising the following steps:

[0064] S1, weighing raw materials of various chemical components according to the chemical composition ratio of the high-strength and high-corrosion-resistant magnesium alloy.

[0065] S2, placing the weighed raw materials of various chemical components in a vacuum induction melting furnace and casting to obtain a target alloy ingot.

[0066] S3, subjecting the target alloy ingot to a solution treatment and then an aging treatment, thereby obtaining the high-strength and high-corrosion-resistant magnesium alloy. Or subjecting the target alloy ingot to a hot extrusion treatment and then an aging treatment, thereby obtaining the high-strength and high-corrosion-resistant magnesium alloy. Or subjecting the target alloy ingot to a hot extrusion treatment and then an aging treatment, thereby obtaining the high-strength and high-corrosion-resistant magnesium alloy.

[0067] In a preferred embodiment of the present invention, the temperature of the solution treatment is 495° C. and the time of the solution treatment is 14 hours to achieve the purpose of solution treatment.

[0068] In a preferred embodiment of the present invention, the temperature of the hot extrusion treatment is 400° C., the extrusion ratio is 9:1, and the extrusion rate is 0.4 mm / s to achieve the purpose of grain refinement.

[0069] In a preferred embodiment of the present invention, the aging treatment temperature is 200° C. and the aging time is 96 hours.

[0070] Compared with the prior art, the present invention has the following beneficial effects:

[0071] The present invention firstly establishes a data set by using the alloying element composition and mechanical properties of the disclosed magnesium alloy, taking the corresponding data of the mechanical properties as input and the alloying element composition as the corresponding output. Then, according to the required mechanical property data as a constraint condition, a first candidate set of microalloying elements and low alloying elements is established from the perspective of the role of alloying elements in precipitation strengthening and fine grain strengthening. At the same time, based on corrosion thermodynamics and kinetics, from the perspective that the formation of a protective film in the corrosion process can be promoted by the asynchronous dissolution and deposition of alloying elements and magnesium elements, the alloying elements are screened under the condition that the microalloying elements satisfy the dissolution order and deposition order are late and the low alloying elements satisfy the dissolution order and deposition order are between the microalloying elements and magnesium elements, and a second candidate set of microalloying elements and low alloying elements is established. According to the several candidate sets of alloying elements obtained above, a candidate high-strength and high-corrosion-resistant Mg-Gd-Y-Zr-In alloy is obtained, so that the present invention improves the corrosion resistance of the alloy material by forming a dense protective film based on the high-strength Mg-Gd-Y-Zr magnesium alloy while retaining the high mechanical strength of the alloy. In addition, according to the commonly used content of alloying elements, the present invention divides the alloying elements in the high-strength magnesium alloy system data set into a micro-alloying element candidate set whose content of alloying elements is less than or equal to the first threshold and a low-alloying element candidate set whose content of alloying elements is greater than the first threshold, so as to form a candidate magnesium alloy with any two alloying elements selected from the micro-alloying element candidate set and any two alloying elements selected from the low-alloying element candidate set and magnesium element. Then, through the corrosion performance prediction model, the candidate magnesium alloy is screened with the constraint conditions that the micro-alloying elements satisfy the latter dissolution order and the former deposition order, the low-alloying elements satisfy the dissolution order and deposition order between the micro-alloying elements and the magnesium element, the nucleation rate of the corrosion product is greater than the corresponding growth rate, the corrosion rate is less than or equal to the second threshold, and the corrosion depth is less than the third threshold, so as to obtain a high-strength and high-corrosion-resistant magnesium alloy.

[0072] The present invention is based on a high-strength magnesium alloy. On the basis of retaining the high mechanical strength of the alloy, the low-alloy elements and micro-alloy elements determined by the above method can densify the protective film produced in the corrosion process through a step-by-step amplification of the nucleation mechanism through the asynchronous dissolution and deposition, forming a multi-layer protective film, realizing alloy passivation, and improving the corrosion resistance of the alloy. Combining corrosion thermodynamics and kinetics, based on the multi-dimensional considerations of "dissolution-ionization-diffusion-deposition", a corrosion performance prediction model is established to further optimize the composition of the alloy and improve the corrosion resistance of the target high-strength and high-corrosion-resistant magnesium alloy in the final design. The magnesium alloy corrosion performance prediction model established in the present invention can calculate the nucleation and growth process of the corrosion products of the alloy during the corrosion process, the coverage of the protective film, and the corrosion rate of the alloy, and can effectively design the alloy composition and predict the corrosion performance of the alloy.

[0073] The present invention proposes a simple and reliable design and development method for a high-strength and high-corrosion-resistant magnesium alloy. Tests show that the high-strength and high-corrosion-resistant magnesium alloy prepared according to the chemical composition of the high-strength and high-corrosion-resistant magnesium alloy designed according to the present invention has a yield strength greater than 200 MPa and a corrosion rate of only 0.17 mm / a in the cast state, and a high-strength and high-corrosion-resistant magnesium alloy obtained by hot extrusion has a yield strength greater than 300 MPa and a corrosion rate less than 0.1 mm / a, and the performance is comparable to that of aluminum alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 This is a standard electrode potential diagram of each alloying element and its compounds in the high-strength and high-corrosion-resistant magnesium alloy of the present invention.

[0075] Figure 2 It is a deposition phase diagram of each alloying element in the high-strength and high-corrosion-resistant magnesium alloy of the present invention.

[0076] Figure 3 These are the corrosion rate test results of Examples 2 to 4 of the present invention and Comparative Examples 1 to 4.

[0077] Figure 4 These are the stress-strain curve test results of Examples 2 to 4 of the present invention and Comparative Examples 1 to 4. DETAILED DESCRIPTION

[0078] The technical solutions in the embodiments of the present invention will be described clearly and completely below.

[0079] Example 1

[0080] This embodiment provides a design method for a high-strength and high-corrosion-resistant magnesium alloy with corrosion thermodynamics, comprising the following steps:

[0081] Step 1, obtain the composition and mechanical properties of the disclosed magnesium alloy, use the corresponding data of the mechanical properties as input, and use the alloy element composition as the corresponding output to establish a data set; wherein the alloy element composition includes the type of alloy element and the content of alloy element; the mechanical property data includes data of mechanical strength and plasticity.

[0082] In this embodiment, the composition of the magnesium alloy includes the alloying elements and their contents in each magnesium alloy.

[0083] Step 2: Evaluate and screen the alloy elements in the first data set according to the two constraints of mechanical strength contribution and plasticity contribution to obtain a high-strength magnesium alloy system data set.

[0084] Step 3: According to the constraints that the content of microalloying elements is ≤1.0% and the content of low alloying elements is 10.0%≥1.0%, the alloying elements in the high-strength magnesium alloy system data set are evaluated and screened to obtain a microalloying element candidate set and a low alloying element candidate set as the first microalloying element candidate set and the low alloying element candidate set, respectively.

[0085] Step 4: Screening to obtain high-strength and high-corrosion-resistant magnesium alloy:

[0086] 4.1) Determine the dissolution order of the corresponding atoms of each alloying element in the candidate magnesium alloy:

[0087] For the high-strength magnesium alloy system data set obtained by screening in step 2 above, the standard electrode potentials of each alloy element are calculated to be And according to the obtained standard electrode potential of each alloy element, the following diagram is drawn: Figure 1 The standard electrode potential diagram of the alloying elements of the Mg-Gd-Y-Zr-In alloy of the present invention is shown in FIG. Figure 1 It can be seen that The dissolution order of each alloy element is Mg≈Gd≈Y>In.

[0089] 4.2) Determine the deposition order of the corresponding atoms of each alloying element in the candidate magnesium alloy:

[0090] For the high-strength magnesium alloy system data set obtained by step 2 above, the following is plotted with pH as the horizontal axis and ion concentration as the vertical axis: Figure 2 The deposition phase diagram of each alloying element in the Mg-Gd-Y-Zr-In alloy shown in the figure is used to determine the deposition order of the alloying elements by using the height of the critical deposition line of each material in the deposition phase diagram.

[0091] And the solubility product K of the corresponding oxide or hydroxide of each alloy element is calculated sp respectively therefore The deposition order of alloying elements is In>Gd>Y>Mg.

[0093] The candidate sets of second micro-alloying elements and low-alloying elements are obtained according to the dissolution sequence and deposition sequence.

[0094] Step 5, according to the screening results of step 3 and step 4, determine that the candidate alloying elements of the microalloying elements are Zr and In, and the candidate alloying elements of the microalloying elements are Gd and Y, and combine the determined candidate alloying elements of the microalloying elements, the candidate alloying elements of the microalloying elements and the magnesium element according to the predefined alloying element mass percentage to form a candidate magnesium alloy: Gd 1.0% ~ 10.0%, Y 1.0% ~ 10.0%, Zr 0.01% ~ 1.0%, In 0.01% ~ 1.0%, and the rest is Mg, totaling 100%.

[0095] Step 6, determining the nucleation rate and growth rate of the corrosion products corresponding to each alloying element in the candidate magnesium alloy, as well as the corrosion rate and corrosion depth of the alloy through the corrosion performance prediction model:

[0096] 6.1) Determine the nucleation rate and growth rate of corrosion products:

[0097] The standard electrode potential of the metal corresponding to each element of the candidate magnesium alloy is used as input, and the equilibrium potential of the metal electrode reaction corresponding to each element is calculated according to the Nernst equation.

[0098] Then, the equilibrium potential of the metal electrode reaction corresponding to each element is used as input, and the corrosion potential of the magnesium alloy is calculated according to the mixed potential theory.

[0099] Then, the corrosion potential of magnesium alloy is taken as input, and the current density under the corrosion potential is calculated according to the Butler-Volmer formula.

[0100] Taking the solubility product of the oxide and hydroxide corresponding to each element as input, the supersaturation S of each corrosion product is calculated according to Faraday's law and Fick's second law.

[0101] Taking the supersaturation S of each corrosion product as input, the nucleation rate and growth rate of the corresponding corrosion product are calculated.

[0102] 6.2) Determine the corrosion rate of corrosion products:

[0103] Taking the nucleation rate and growth rate of corrosion products as input, the coverage of corrosion products and the overall corrosion rate of magnesium alloy are calculated.

[0104] 6.3) Determine the corrosion depth of corrosion products:

[0105] The corrosion depth of magnesium alloy is calculated by taking the overall corrosion rate and corrosion current density of magnesium alloy as input.

[0106] With the micro-alloying elements satisfying the dissolution order at the end and the deposition order at the beginning, the low-alloying elements satisfying the dissolution order and the deposition order both being between the micro-alloying elements and the magnesium element, the nucleation rate of the corrosion products being greater than the corresponding growth rate, the corrosion rate rapidly decreasing to ≤1 mm / a with time, and the corrosion depth being <5 μm as the constraint conditions, the candidate magnesium alloys obtained above are screened to obtain the desired high-strength and high-corrosion-resistant magnesium alloy, and the chemical composition of the obtained high-strength and high-corrosion-resistant magnesium alloy consists of the following components in percentage by mass: Gd 6%, Y 3%, Zr 0.5%, In 0.5%, and the rest being Mg, totaling 100%, recorded as Mg-6Gd-3Y-0.5Zr-0.5In alloy.

[0107] Example 2

[0108] This embodiment provides a method for preparing a high-strength and high-corrosion-resistant magnesium alloy, comprising the following steps:

[0109] S1, according to the chemical composition ratio of the high-strength and high-corrosion-resistant alloy screened in Example 1, i.e., Mg-6Gd-3Y-0.5Zr-0.5In alloy, weigh the corresponding Gd source, Y source, Zr source, In source and Mg source:

[0110] Gd 6%, Y 3%, Zr 0.5%, In 0.5%, and the remainder Mg, totaling 100%.

[0111] Among them, the Gd source used in this embodiment is added in the form of an intermediate alloy Mg-25Gd, the Y source is added in the form of an intermediate alloy Mg-25Y, the Zr source is added in the form of an intermediate alloy Mg-20Zr, the In source is added in the form of pure In particles, and the Mg source is added in the form of intermediate alloys Mg-25Gd, Mg-25Y, Mg-20Zr and pure magnesium.

[0112] S2, placing the weighed raw materials of various chemical components in a graphite crucible for vacuum induction melting, heating them under the protection of a mixed gas of CO2 and SF6 with a volume ratio of 9:1, heating to 720°C and then keeping warm for 30 minutes to ensure that the raw materials are completely melted, applying mechanical stirring for 10 minutes after melting to ensure that the raw materials are evenly mixed, standing for 20 minutes after stirring, and finally pouring them into a stainless steel mold to obtain a cylindrical ingot of Φ100mm×600mm to obtain the target alloy ingot.

[0113] S3, homogenizing the obtained target alloy ingot with solid solution treatment at a temperature of 495°C, keeping the temperature for 14 hours and then cooling with hot water at about 80°C. Then, the solution treated sample is subjected to aging treatment at a temperature of 200°C and an aging time of 96 hours.

[0114] S4, the samples after aging treatment were processed by wire cutting into 20mm×20mm×5mm specimens and sheet-shaped dog-bone tensile specimens with a gauge length of 15mm, a width of 3.6mm, and a thickness of 2.5mm, which were used for hydrogen evolution test and room temperature tensile test respectively. Before the test, 240#, 600#, 1000# and 2000# SiC sandpaper were used for grinding in turn.

[0115] Example 3

[0116] This embodiment provides a method for preparing a high-strength and high-corrosion-resistant magnesium alloy, comprising the following steps:

[0117] S1, according to the chemical composition ratio of the high-strength and high-corrosion-resistant alloy screened in Example 1, i.e., Mg-6Gd-3Y-0.5Zr-0.5In alloy, weigh the corresponding Gd source, Y source, Zr source, In source and Mg source:

[0118] Gd 6%, Y 3%, Zr 0.5%, In 0.5%, and the remainder Mg, totaling 100%.

[0119] Among them, the Gd source used in this embodiment is added in the form of an intermediate alloy Mg-25Gd, the Y source is added in the form of an intermediate alloy Mg-25Y, the Zr source is added in the form of an intermediate alloy Mg-20Zr, the In source is added in the form of pure In particles, and the Mg source is added in the form of intermediate alloys Mg-25Gd, Mg-25Y, Mg-20Zr and pure magnesium.

[0120] S2, placing the weighed raw materials of various chemical components in a graphite crucible for vacuum induction melting, heating them under the protection of a mixed gas of CO2 and SF6 with a volume ratio of 9:1, heating to 720°C and then keeping warm for 30 minutes to ensure that the raw materials are completely melted, applying mechanical stirring for 10 minutes after melting to ensure that the raw materials are evenly mixed, standing for 20 minutes after stirring, and finally pouring them into a stainless steel mold to obtain a cylindrical ingot of Φ100mm×600mm to obtain the target alloy ingot.

[0121] S3, hot extrusion treatment is performed on the obtained target alloy ingot, the extrusion temperature is 400°C, the extrusion ratio is 9:1, the extrusion rate is 0.4 mm / s, and an extruded rod with a diameter of 30 mm is obtained.

[0122] S4, the samples after hot extrusion treatment were processed by wire cutting into 20mm×20mm×5mm specimens and sheet-shaped dog-bone tensile specimens with a gauge length of 15mm, a width of 3.6mm, and a thickness of 2.5mm, which were used for hydrogen evolution test and room temperature tensile test respectively. Before the test, 240#, 600#, 1000# and 2000# SiC sandpaper were used for grinding in turn.

[0123] Example 4

[0124] This embodiment provides a method for preparing a high-strength and high-corrosion-resistant magnesium alloy, comprising the following steps:

[0125] S1, according to the chemical composition ratio of the high-strength and high-corrosion-resistant magnesium alloy screened in Example 1, i.e., Mg-6Gd-3Y-0.5Zr-0.5In alloy, weigh the corresponding Gd source, Y source, Zr source, In source and Mg source:

[0126] Gd 6%, Y 3%, Zr 0.5%, In 0.5%, and the remainder Mg, totaling 100%.

[0127] Among them, the Gd source used in this embodiment is added in the form of an intermediate alloy Mg-25Gd, the Y source is added in the form of an intermediate alloy Mg-25Y, the Zr source is added in the form of an intermediate alloy Mg-20Zr, the In source is added in the form of pure In particles, and the Mg source is added in the form of intermediate alloys Mg-25Gd, Mg-25Y, Mg-20Zr and pure magnesium.

[0128] S2, placing the weighed raw materials of various chemical components in a graphite crucible for vacuum induction melting, heating them under the protection of a mixed gas of CO2 and SF6 with a volume ratio of 9:1, heating to 720°C and then keeping warm for 30 minutes to ensure that the raw materials are completely melted, applying mechanical stirring for 10 minutes after melting to ensure that the raw materials are evenly mixed, standing for 20 minutes after stirring, and finally pouring them into a stainless steel mold to obtain a cylindrical ingot of Φ100mm×600mm to obtain the target alloy ingot.

[0129] S3, hot extrusion treatment is performed on the obtained target alloy ingot, the extrusion temperature is 400°C, the extrusion ratio is 9:1, and the extrusion rate is 0.4mm / s, to obtain an extruded rod with a diameter of 30mm; then aging treatment is performed, the aging temperature is 200°C, and the aging time is 96h.

[0130] S4, the samples after aging treatment were processed by wire cutting into 20mm×20mm×5mm specimens and sheet-shaped dog-bone tensile specimens with a gauge length of 15mm, a width of 3.6mm, and a thickness of 2.5mm, which were used for hydrogen evolution test and room temperature tensile test respectively. Before the test, 240#, 600#, 1000# and 2000# SiC sandpaper were used for grinding in turn.

[0131] Comparative Example 1

[0132] The difference between this comparative example and Example 2 is only that:

[0133] The chemical composition ratio of the alloy components in this comparative example is:

[0134] Gd 6%, Y 3%, Zr 0.5%, and the remainder Mg, totaling 100%, the alloy of this comparative example is recorded as Mg-6Gd-3Y-0.5Zr alloy.

[0135] Comparative Example 2

[0136] The difference between this comparative example and Example 3 is only that:

[0137] The chemical composition ratio of the alloy components in this comparative example is:

[0138] Gd 6%, Y 3%, Zr 0.5%, and the remainder Mg, totaling 100%, the alloy of this comparative example is recorded as Mg-6Gd-3Y-0.5Zr alloy.

[0139] Comparative Example 3

[0140] The difference between this comparative example and Example 4 is only that:

[0141] The chemical composition ratio of the alloy components in this comparative example is:

[0142] Gd 6%, Y 3%, Zr 0.5%, and the remainder Mg, totaling 100%, the alloy of this comparative example is recorded as Mg-6Gd-3Y-0.5Zr alloy.

[0143] Comparative Example 4

[0144] In this comparative example, commercial AZ91D magnesium alloy was used as the control group.

[0145] Experimental Section

[0146] The present invention takes the magnesium alloys of Examples 2 to 4 and Comparative Examples 1 to 4 as examples and conducts the following tests thereon respectively.

[0147] 1) Corrosion performance test

[0148] The present invention tests the corrosion performance of the magnesium alloy samples of Examples 2 to 4 and Comparative Examples 1 to 4 respectively according to ASTM G31-72 "Laboratory Immersion Corrosion Standard for Metals", and the test results are as follows: Figure 3 shown.

[0149] Depend on Figure 3 It can be seen that the corrosion rate of the magnesium alloy sample of Example 2 is 0.17±0.01 mm / a, while Comparative Example 1 does not conform to the design principle of the present invention and has very poor corrosion resistance. Compared with Comparative Example 1, the corrosion resistance of the high-strength and high-corrosion-resistant magnesium alloy designed by the present invention is improved by 53 times.

[0150] The corrosion rate of the magnesium alloy sample of Example 3 is 0.09±0.02 mm / a. Compared with Comparative Example 2, the high-strength and high-corrosion-resistant magnesium alloy designed in Example 2 is significantly improved.

[0151] The corrosion rate of the magnesium alloy sample of Example 4 is 0.08±0.01 mm / a. Compared with Comparative Example 3, the corrosion resistance of the high-strength and high-corrosion-resistant magnesium alloy designed in Example 3 is improved by 127 times.

[0152] Based on the above, compared with the corrosion rates of Comparative Examples 1 to 4, the corrosion rates of Examples 2 to 4 of the present invention are significantly improved, indicating that the high-strength and high-corrosion-resistant magnesium alloy designed by the present invention has excellent corrosion resistance.

[0153] 2) Mechanical properties test

[0154] The present invention tests the stress-strain curves of the magnesium alloy samples of Examples 2 to 4 and Comparative Examples 1 to 4 in accordance with GB / T 228-2002 "Room Temperature Tensile Method for Metallic Materials", and the test results are as follows: Figure 4 shown.

[0155] And by Figure 4 It can be seen that the yield strength, tensile strength and elongation at break of the magnesium alloy sample of Example 2 are 205.35±2.63MPa, 259.51±20.24MPa and 5.73±1.53% respectively. Compared with Comparative Example 1, the high-strength and high-corrosion-resistant magnesium alloy designed by the present invention has excellent mechanical strength.

[0156] The yield strength, tensile strength and elongation at break of the magnesium alloy sample of Example 3 are 239.33±1.70MPa, 311.70±2.93MPa and 25.84±0.79% respectively. Compared with Comparative Example 2, the high-strength and high-corrosion-resistant magnesium alloy designed by the present invention has excellent mechanical strength.

[0157] The yield strength, tensile strength and elongation at break of the magnesium alloy sample of Example 4 are 320.77±1.70 MPa, 377.34±0.78 MPa and 14.99±0.08% respectively. Compared with Comparative Example 3, the high-strength and high-corrosion-resistant magnesium alloy designed by the present invention has excellent mechanical strength.

[0158] Based on the above, compared with the mechanical strength of Comparative Examples 1 to 4, the mechanical strength of Examples 1 to 3 of the present invention are significantly improved, indicating that the high-strength and high-corrosion-resistant magnesium alloy designed by the present invention has excellent corrosion resistance.

[0159] In summary, the high-strength and high-corrosion-resistant magnesium alloy designed in the present invention has excellent mechanical properties and corrosion resistance.

[0160] It should be emphasized that the above embodiments are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the content of alloy elements can be adjusted. Any adjustment of the element content or process parameters in accordance with the principles of the present invention should be included in the protection scope of the present invention.

[0161] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A design method for high-strength and high-corrosion-resistant magnesium alloy based on corrosion thermodynamics, characterized in that: The following steps are involved: Obtain the alloying element composition and mechanical properties of the disclosed magnesium alloy, take the corresponding data of the mechanical properties as input, take the alloying element composition as the corresponding output, and establish a data set; wherein the alloying element composition is the type of alloying element and the content of alloying element; Taking the required mechanical property data as a constraint condition, the data set is screened to obtain a high-strength magnesium alloy system data set; According to the constraint condition that the content of the alloying element is ≤ the first threshold, the alloying elements in the high-strength magnesium alloy system data set are screened to obtain a candidate set of the first micro-alloying element and the low-alloying element; Based on corrosion thermodynamics and kinetics, the alloying elements in the high-strength magnesium alloy system data set are screened to obtain a candidate set of the second micro-alloying element and the low-alloying element, with the constraint that the micro-alloying element satisfies the dissolution order of the latter and the deposition order of the former, and the low-alloying element satisfies the dissolution order and deposition order of the latter both being between the micro-alloying element and the magnesium element; Determine candidate alloying elements of microalloying elements and low alloying elements based on the first candidate set of microalloying elements and low alloying elements and the second candidate set of microalloying elements and low alloying elements, and combine the candidate alloying elements with magnesium element according to the predefined alloying element mass percentage to form a candidate magnesium alloy; Determining the nucleation rate and growth rate of the corrosion products corresponding to each alloying element in the candidate magnesium alloy, as well as the corrosion rate and corrosion depth of the alloy by using a corrosion performance prediction model; The candidate magnesium alloys are screened with the constraints that the nucleation rate of the corrosion product is greater than the corresponding growth rate, the corrosion rate is less than or equal to the second threshold, and the corrosion depth is less than the third threshold to obtain a high-strength and high-corrosion-resistant magnesium alloy.

2. The design method according to claim 1, characterized in that: The mechanical property data are data of mechanical strength contribution and plasticity contribution.

3. The design method according to claim 1, characterized in that: By obtaining the standard electrode potentials of the metals corresponding to the alloy elements and sorting them in descending order, the dissolution order of the atoms corresponding to each alloy element can be determined; The deposition order of magnesium alloy corrosion products is determined by obtaining the solubility products of the oxides or hydroxides corresponding to the alloying elements and arranging them in order according to the height of the critical deposition lines of the oxides or hydroxides corresponding to the alloying elements.

4. The design method according to claim 1, characterized in that: The corrosion performance prediction model is a "dissolution-ionization-diffusion-deposition" model, and the "dissolution-ionization-diffusion-deposition" model is obtained by the following steps: Taking the standard electrode potential of the metal corresponding to each element of the candidate magnesium alloy as input, according to the Nernst equation, the equilibrium potential of the metal electrode reaction corresponding to each element of the candidate magnesium alloy is calculated; then taking the equilibrium potential of the metal electrode reaction corresponding to each element as input, according to the mixed potential theory, the corrosion potential of the magnesium alloy is calculated; then taking the corrosion potential of the magnesium alloy as input, according to the Butler-Volmer formula, the corrosion current density of the magnesium alloy under the corrosion potential is calculated; Taking the solubility product of the oxide and hydroxide of each element as input, according to Faraday's law and Fick's second law, the supersaturation of each corrosion product is calculated; taking the supersaturation of each corrosion product as input, the nucleation rate and growth rate of the corresponding corrosion product are calculated; The overall corrosion rate of the candidate magnesium alloy is calculated by taking the nucleation rate and growth rate of the corrosion products as input; The overall corrosion rate and corrosion current density of the magnesium alloy are used as input to calculate the corrosion depth of the candidate magnesium alloy.

5. A high-strength and high-corrosion-resistant magnesium alloy obtained by screening according to the design method of any one of claims 1 to 4, characterized in that: The high-strength and high-corrosion-resistant magnesium alloy screened is a Mg-Gd-Y-Zr-In alloy, and its chemical composition in terms of mass percentage is: Gd 1.0% to 10.0%, Y 1.0% to 10.0%, Zr 0.01% to 1.0%, In 0.01% to 1.0%, and the rest is Mg, totaling 100%.

6. A method for preparing the high-strength and high-corrosion-resistant magnesium alloy according to claim 5, characterized in that: The steps include: According to the chemical composition ratio of the high-strength and high-corrosion-resistant magnesium alloy, weigh the raw materials of the corresponding mass of each chemical component; The weighed raw materials of various chemical components are placed in a vacuum induction melting furnace and cast to obtain a target alloy ingot; The target alloy ingot is subjected to a solution treatment and then an aging treatment to obtain the high-strength and high-corrosion-resistant magnesium alloy; or subjecting the target alloy ingot to hot extrusion treatment to obtain the high-strength and high-corrosion-resistant magnesium alloy; Alternatively, the target alloy ingot is subjected to hot extrusion treatment and then aging treatment to obtain the high-strength and high-corrosion-resistant magnesium alloy.

7. The preparation method according to claim 6, characterized in that: The temperature of the solution treatment is 490° C. to 500° C., and the time of the solution treatment is 12 h to 16 h.

8. The preparation method according to claim 6, characterized in that: The temperature of the hot extrusion treatment is 380° C. to 420° C., and the extrusion ratio is 8 to 10:

1.

9. The preparation method according to claim 6, characterized in that: The extrusion rate of the hot extrusion process is 0.3 mm / s to 0.5 mm / s.

10. The preparation method according to claim 6, characterized in that: The temperature of the aging treatment is 180° C. to 220° C., and the aging time is 72 h to 120 h.

Citation Information

Patent Citations

  • Functional rapidly soluble rare earth magnesium alloy material and preparation method thereof

    CN109161769A

  • Preparation method of magnesium alloy with ternary rare earth conversion films with different weight percentages on surface and obtained magnesium alloy

    CN114388068A

  • Reverse design method of high-performance magnesium alloy based on machine learning

    CN116844673A

  • Magnesium alloy intelligent development method and magnesium alloy performance intelligent prediction method

    CN118888057A

  • Super-corrosion-resistant magnesium alloy and preparation method therefor

    WO2024208130A1

Cited By

  • Design method for improving corrosion resistance of copper-nickel alloy by adding alloy elements

    CN120673920A